A Comparative Study of Science Teaching Through Traditional Method and 5E Models at Secondary Level: A comparison of the effectiveness of 5E Learning Cycle and traditional teaching methods on student achievement and engagement in secondary level science courses (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Two third-grade science courses were examined in this study to see if the 5E Learning Cycle or traditional teaching methods were more effective in enhancing student achievement, interest, and engagement. A three-week 5E Learning Cycle unit and a three-week traditional teaching method unit were completed by both classes. The 5E Learning Cycle units had greater student scores, interest, and engagement than the traditional teaching method components.